Czy prawo powinno być neutralne moralnie? Uwagi na temat unormowania sztucznej inteligencji - Wyszyński, Filip (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This article discusses the issues concerning artificial intelligence regulation. The need to regulate artificial intelligence was indicated. The author postulates a morally neutral law for AI algorithms. The proposal to regulate artificial intelligence by means of morally neutral law is based on the philosophy of law theory by Axel Hägerström and Ronald Dworkin. It is about a independence of an artificial intelligence from state power instruments. The study concludes that there is a need to regulate artificial intelligence for the sake of protecting humans from human and AI threats.
Keywords: artificial intelligence; morality; neutrality